Evolution of the temperature field on an absorber irradiated by an intense ion beam; Soviet Physics Journal; Vol. 29, iss. 5 - Boyko (Boiko) V. I. Vladimir Ilyich; Evstigneev V. V. Vladimir Vasilievich; Prilepskikh N. N.; Shamanin I. V. Igor Vladimirovich (1986, 1986)
Title screen